Analisis Kepuasan Pelanggan Dalam Berbelanja Online Di Kalangan Mahasiswa - Dellawati; Frischa Anggraeni; Syamsul Hidayat (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2024)
Technology changes times, this change will be followed by increasing needs and different desires, especially shopping needs. Online shopping makes it easier for us to shop without spending time and energy. Online shopping activities can be done via smartphone, tablet, laptop connected to the internet network. This study aims to analyze consumer satisfaction in online shopping among students with the causal factors and consequences that will arise using quantitative or statistical methods as research subjects. The research sample consisted of 171 respondents. This research instrument is in the form of a questionnaire, developed based on instruments that have been used by other researchers and tested for validity and reliability before being distributed to respondents in this research. Thus, this approach will allow analysts to find out the extent of consumer behavior towards satisfaction in online shopping among Management students at Bina Bangsa University in the city of Serang. The results of the analysis show that all the hypotheses of this research are proven. In other words, site characteristics such as convenience, informativeness, security and communication have a significant effect on customer satisfaction.